Optical Film

By using a glass film and polarizing plate structure with moderate thickness in the optical film and controlling the difference in strain value of the polarizing plate, the problem of cracks at the end of the glass film elongation in a humidified environment is solved, and the durability of the optical film is improved.

CN114514452BInactive Publication Date: 2025-02-28NITTO DENKO CORP
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202080066844.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-09-16
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, after being processed to a predetermined size, the glass film is prone to cracks at the ends and elongates under a humidified environment, resulting in durability problems of the optical film.

Method used

A glass film having a thickness of 50 μm or more and 150 μm or less is adopted, and a structure of a polarizing plate, a polarizing plate and a protective film is combined with the structure of a polarizing plate, a polarizing plate and a protective film, and the elongation of cracks at the end of the glass film is controlled within a specific range by controlling the difference in the strain value between the MD direction and the TD direction on the polarizing plate.

Benefits of technology

Even if there are cracks of a predetermined size at the end of the glass film, the optical film can effectively suppress the elongation of the cracks under a predetermined temperature and humidity environment, and improve the durability of the optical film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114514452B_ABST
    Figure CN114514452B_ABST
Patent Text Reader

Abstract

The optical film comprises a glass film and a polarizing plate, wherein the glass film has a thickness of 50 μm or more and 150 μm or less, and has a crack with a length of 20 μm or more at an end of the glass film; the polarizing plate comprises a polarizer and a protective film disposed on at least one surface of the polarizer; and the absolute value of the difference between the strain amount in the MD direction and the strain amount in the TD direction of the polarizing plate under a constant temperature and humidity environment of 60° C. and 90% humidity is 0 or more and 40×10 ‑6 the following.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an optical film. Background Art

[0002] In recent years, liquid crystal display elements or display elements using organic EL (Organic Electro-Luminescence) are becoming lighter and thinner from the perspective of storage and design. Conventionally, a cover glass is used as the outermost surface of the display element, and after the polarizing plate is attached to the liquid crystal unit, etc., the cover glass is set on the polarizing plate via an interlayer filler.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2019 / 087938 Summary of the invention

[0006] Problems to be solved by the invention

[0007] On the other hand, efforts have been made to simplify the process of laminating a cover glass and a polarizing plate via an interlayer filler by previously integrating an extremely thin glass (glass film) and the polarizing plate and laminating them to a liquid crystal cell or the like.

[0008] Patent document 1 discloses a technology in which a glass film laminate having excellent strength and flexibility against contact with a protrusion having a high hardness such as a pen is used as the outermost layer of a display element or a lighting element. Specifically, an optical film is proposed, which is a glass film laminate for a display element, and is sequentially laminated with a glass film, an adhesive layer, a protective film, a polarizer, and an adhesive layer.

[0009] Here, the inventors processed a glass film laminate into a predetermined size by laser or cutting for use in a notebook personal computer, attached it to a display element, and conducted a durability test in a humid environment, etc. As a result, it was found that when it was processed into a predetermined size, cracks were generated at the ends of the glass film, and the cracks extended in a humid environment, etc.

[0010] In view of the above problems, an object of the present invention is to provide an optical film capable of suppressing the extension of cracks under a predetermined temperature and humidity environment even if cracks of a predetermined size exist at the end of a glass film.

[0011] Solutions to the problem

[0012] The optical film comprises a glass film and a polarizing plate, wherein the glass film has a thickness of 50 μm or more and 150 μm or less, and has a crack with a length of 20 μm or more at an end of the glass film; the polarizing plate comprises a polarizer and a protective film disposed on at least one surface of the polarizer; and the absolute value of the difference between the strain amount in the MD direction and the strain amount in the TD direction of the polarizing plate under a constant temperature and humidity environment of 60° C. and 90% humidity is 0 or more and 40×10 -6 the following.

[0013] Effects of the Invention

[0014] The disclosed technology can provide an optical film capable of suppressing the extension of cracks under a predetermined temperature and humidity environment even if cracks of a predetermined size exist at the end of a glass film. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 FIG. 1 is a cross-sectional view schematically showing an optical film according to the first embodiment.

[0016] Figure 2 FIG. 2 is a cross-sectional view exemplarily showing an optical film according to the second embodiment.

[0017] Figure 3 It is a figure which shows the attachment position of a strain gauge.

[0018] Figure 4 This is a diagram for explaining examples and comparative examples (part 1).

[0019] Figure 5 This is a diagram for explaining examples and comparative examples (part 2).

[0020] Figure 6 It is a figure (part 3) for explaining an Example and a comparative example.

[0021] Explanation of symbols

[0022] 10, 10A optical film;

[0023] 11 Glass film;

[0024] 12 adhesive layer;

[0025] 13 polarizing plate;

[0026] 14, 15 adhesive layer;

[0027] 131 Polarizer;

[0028] 132 Protective film. DETAILED DESCRIPTION

[0029] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. In each of the drawings, the same components are denoted by the same reference numerals, and overlapping descriptions may be omitted.

[0030] <First Embodiment>

[0031] Figure 1 2 is a cross-sectional view schematically showing an optical film according to the first embodiment. Figure 1 The optical film 10 includes a glass film 11 , an adhesive layer 12 , a polarizing plate 13 , and an adhesive layer 14 in sequence.

[0032] It should be noted that, in this specification, the adhesive layer refers to a layer that has adhesiveness at room temperature and adheres to an adherend under a relatively light pressure. Therefore, when the adherend attached to the adhesive layer is peeled off, the adhesive layer also maintains practical adhesion. On the other hand, the adhesive layer refers to a layer that can combine substances by being between substances. Therefore, when the adherend attached to the adhesive layer is peeled off, the adhesive layer does not have practical adhesion.

[0033] The polarizing plate 13 includes a polarizer 131 and a protective film 132. The protective film 132 is disposed on at least one side (one surface) of the polarizer 131. Although the protective film 132 is preferably disposed at least on the adhesive layer 12 side of the polarizer 131, it may be disposed on both sides (one surface and the other surface) of the polarizer 131 as required.

[0034] It should be noted that, as required, a phase difference layer can be arranged on the side of the polarizing plate 13 opposite to the adhesive layer 12. The phase difference layer can be laminated on the polarizing plate 13 via any appropriate adhesive layer or adhesive layer. In addition, as required, a release film can be arranged on the side opposite to the polarizing plate 13 via the adhesive layer 14.

[0035] Hereinafter, each component of the optical film 10 will be described in more detail.

[0036] [Glass film]

[0037] There is no particular limitation on the glass film 11, and an appropriate glass film can be used according to the purpose. Regarding the glass film 11, according to the classification based on the composition, for example, soda-lime glass, borate glass, aluminosilicate glass, quartz glass, etc. can be cited. In addition, according to the classification based on the alkaline component, non-alkaline glass and low-alkaline glass can be cited. The content of the alkali metal component (such as Na2O, K2O, Li2O) of the above-mentioned glass is preferably 15% by weight or less, and more preferably 10% by weight or less.

[0038] The thickness of the glass film 11 is preferably 50 μm to 150 μm, more preferably 60 μm to 140 μm, further preferably 70 μm to 130 μm, and particularly preferably 80 μm to 120 μm. Within this range, the glass film 11 has excellent flexibility and can be processed by a roll-to-roll process, and an optical film 10 that is difficult to break and has excellent productivity can be obtained.

[0039] The light transmittance of the glass film 11 at a wavelength of 550 nm is preferably 85% or more. The refractive index of the glass film 11 at a wavelength of 550 nm is preferably 1.4 to 1.65.

[0040] The density of the glass film 11 is preferably 2.3 g / cm 3 ~3.0g / cm 3 , more preferably 2.3 g / cm 3 ~2.7g / cm 3 When the glass film has a content within the above range, it is possible to provide an optical film 10 that contributes to weight reduction of an image display device or the like.

[0041] There is no particular limitation on the forming method of the glass film 11, and an appropriate forming method can be adopted according to the purpose. As a representative method, the glass film 11 can be produced by melting a mixture containing a main raw material such as silica or alumina, a defoaming agent such as sodium sulfate or antimony oxide, and a reducing agent such as carbon at a temperature of about 1400°C to 1600°C, forming it into a thin plate, and then cooling it. As the forming method of the glass film 11, for example, a flow hole down-drawing method, a melting method, a floating glass plate method, etc. can be cited. Regarding the glass film formed by these methods, in order to thin the plate or improve the smoothness, chemical polishing can be performed using a solvent such as hydrofluoric acid as needed.

[0042] [Adhesive layer]

[0043] There is no particular limitation on the adhesive layer 12, and appropriate adhesives can be used according to the purpose. As adhesives, for example, polyester adhesives, polyurethane adhesives, polyvinyl alcohol adhesives, and epoxy adhesives can be cited. Among them, epoxy adhesives that can obtain particularly good adhesion are preferred.

[0044] When the adhesive layer 12 is a thermosetting adhesive, it can be hardened (cured) by heating to exert anti-peeling force. In addition, when the adhesive layer 12 is a light-curing adhesive such as an ultraviolet curing adhesive, it can be hardened by irradiating light such as ultraviolet rays to exert anti-peeling force. In addition, when the adhesive layer 12 is a moisture-curing adhesive, it can react with moisture in the air to harden, so it can be hardened even if it is left alone to exert anti-peeling force.

[0045] As the adhesive layer 12 , for example, a commercially available adhesive may be used, or an adhesive solution (or dispersion) may be prepared by dissolving or dispersing various curable resins in a solvent.

[0046] The thickness of the adhesive layer 12 is preferably 10 μm or less, more preferably 0.1 μm to 10 μm, further preferably 0.5 μm to 8 μm, and particularly preferably 1 μm to 6 μm. Within this range, an optical film 10 having excellent flexibility and excellent puncture resistance can be obtained.

[0047] The elastic modulus of the adhesive layer 12 is preferably 0.5 GPa to 15 GPa, more preferably 0.8 GPa to 10 GPa, and further preferably 1 GPa to 5 GPa. Within this range, an optical film 10 having excellent flexibility and excellent puncture resistance can be obtained. In this specification, the elastic modulus can be measured using an automatic plotter under the following conditions.

[0048] [Elastic modulus measurement method]

[0049] Measurement temperature: 25℃

[0050] Sample size: width 2cm, length 15cm

[0051] Distance between chucks: 10cm

[0052] Stretching speed: 10mm / min.

[0053] [Polarizing plate]

[0054] The thickness of the polarizing plate 13 is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm, further preferably 25 μm to 200 μm, and particularly preferably 25 μm to 100 μm.

[0055] The elastic modulus of the polarizing plate 13 is preferably 1 GPa or more, more preferably 1 GPa to 10 GPa, further preferably 2 GPa to 7 GPa, and particularly preferably 2 GPa to 5 GPa. Within this range, an optical film 10 having excellent puncture resistance can be obtained.

[0056] There is no particular limitation on the shape of the polarizing plate 13, and an appropriate shape can be adopted according to the purpose. As an example, a square shape with long sides and short sides can be cited. In the case where the polarizing plate 13 is square, it is preferred that the absorption axis direction of the polarizer 131 of the polarizing plate 13 is roughly parallel to the long side or short side of the polarizing plate 13. It should be noted that in this specification, "roughly parallel" is a concept that includes not only the case of strict parallelism, but also the case where the angle formed by the two lines is ±10° (preferably ±5°).

[0057] [Polarizer]

[0058] There is no particular limitation on the thickness of the polarizer 131, and an appropriate thickness can be adopted according to the purpose. The typical thickness of the polarizer 131 is about 1 μm to 80 μm. A thin polarizer can be used as the polarizer 131, in which case the thickness of the polarizer 131 is preferably 20 μm or less, more preferably 15 μm or less, further preferably 10 μm or less, and particularly preferably 5 μm or less.

[0059] The polarizer 131 preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 40.0% or more, more preferably 41.0% or more, further preferably 42.0% or more, and particularly preferably 43.0% or more. The polarization degree of the polarizer 131 is preferably 99.8% or more, more preferably 99.9% or more, and further preferably 99.95% or more.

[0060] The polarizer 131 is preferably an iodine-based polarizer. More specifically, the polarizer may be formed of a polyvinyl alcohol-based resin (hereinafter referred to as "PVA-based resin") film containing iodine.

[0061] The PVA-based resin used for forming the PVA-based resin film is not particularly limited, and an appropriate resin may be adopted depending on the purpose. Examples of the resin include polyvinyl alcohol and ethylene-vinyl alcohol copolymers.

[0062] Polyvinyl alcohol can be obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymer can be obtained by saponifying ethylene-vinyl acetate copolymer. The saponification degree of PVA resin is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. The saponification degree is obtained according to JISK 6726-1994. By using the PVA resin with the saponification degree, a polarizer with excellent durability can be obtained. If the saponification degree is too high, gelation is likely to occur.

[0063] The average degree of polymerization of the PVA resin is not particularly limited and can be appropriately selected according to the purpose. The average degree of polymerization of the PVA resin is, for example, 1000 to 10000, preferably 1200 to 5000, and more preferably 1500 to 4500. The average degree of polymerization is determined according to JIS K 6726-1994.

[0064] As a method for manufacturing the polarizer 131, for example, there can be cited a method (I) of stretching and dyeing a PVA-based resin film monomer, a method (II) of stretching and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol-based resin layer, etc. Since method (I) is a well-known and commonly used method in the art, its detailed description is omitted.

[0065] Method (II) preferably includes: stretching and dyeing a laminate (i) having a resin substrate and a polyvinyl alcohol-based resin layer formed on one side of the resin substrate to prepare a polarizer on the resin substrate. The laminate (i) can be formed by applying a coating solution containing a polyvinyl alcohol-based resin on a resin substrate and drying it. In addition, the laminate (i) can be formed by transferring the polyvinyl alcohol-based resin layer to a resin substrate. The details of the above-mentioned manufacturing method (II) are described in, for example, Japanese Patent Publication No. 2012-73580, and the publication can be cited in this specification as a reference.

[0066] [Protective film]

[0067] As the protective film 132, there is no particular limitation, and suitable resin films can be adopted according to the purpose. As the formation material of the protective film 132, for example, polyester resins such as polyethylene terephthalate (PET), cellulose resins such as triacetyl cellulose (TAC), cycloolefin resins such as norbornene resins, olefin resins such as polyethylene, polypropylene, (meth) acrylic resins, etc. can be cited. Among them, preferably polyethylene terephthalate (PET). It should be noted that, "(meth) acrylic resin" refers to acrylic resin and / or methacrylic resin.

[0068] As the (meth)acrylic resin, for example, a (meth)acrylic resin having a glutarimide structure is used. The (meth)acrylic resin having a glutarimide structure (hereinafter also referred to as glutarimide resin) is described in, for example, Japanese Patent Application Laid-Open No. 2006-309033, Japanese Patent Application Laid-Open No. 2006-317560, Japanese Patent Application Laid-Open No. 2006-328329, Japanese Patent Application Laid-Open No. 2006-328334, Japanese Patent Application Laid-Open No. 2006-337491, Japanese Patent Application Laid-Open No. 2006-337492, Japanese Patent Application Laid-Open No. 2006-337493, Japanese Patent Application Laid-Open No. 2006-337569, Japanese Patent Application Laid-Open No. 2007-009182, Japanese Patent Application Laid-Open No. 2009-161744, and Japanese Patent Application Laid-Open No. 2010-284840. These descriptions can be cited in this specification as a reference.

[0069] The protective film 132 and the polarizer 131 may be laminated via any appropriate adhesive layer. Before or after laminating the protective film 132 and the polarizer 131 , the resin substrate used in manufacturing the polarizer 131 is peeled off.

[0070] The thickness of the protective film 132 is preferably 4 μm to 250 μm, more preferably 5 μm to 150 μm, further preferably 10 μm to 100 μm, and particularly preferably 10 μm to 50 μm.

[0071] The elastic modulus of the protective film 132 is 1 GPa or more, preferably 1 GPa to 10 GPa, more preferably 1.8 GPa to 7 GPa, and further preferably 2 GPa to 5 GPa. Within this range, an optical film 10 having excellent puncture resistance can be obtained.

[0072] [Phase difference layer]

[0073] As described above, the phase difference layer is not a necessary structure, but is provided as needed. In the case where a phase difference layer is provided, the phase difference layer is not particularly limited and can have any appropriate optical properties and / or mechanical properties according to the purpose. The phase difference layer usually has a slow axis. The optical properties and / or mechanical properties of the phase difference layer can be appropriately selected according to the orientation mode of the liquid crystal unit.

[0074] The phase difference layer may exhibit reverse dispersion characteristics in which the phase difference value increases with the wavelength of the measuring light, positive dispersion characteristics in which the phase difference value decreases with the wavelength of the measuring light, or flat dispersion characteristics in which the phase difference value hardly changes with the wavelength of the measuring light.

[0075] The thickness of the retardation layer is preferably 60 μm or less, more preferably 30 μm to 55 μm, and even more preferably 30 μm or less.

[0076] The phase difference layer can be composed of any appropriate resin film that can satisfy the above characteristics. Representative examples of such resins include cycloolefin resins, polycarbonate resins, cellulose resins, polyester resins, polyvinyl alcohol resins, polyamide resins, polyimide resins, polyether resins, polystyrene resins, acrylic resins, and polymer liquid crystal resins.

[0077] [Adhesive layer]

[0078] The adhesive layer 14 can be formed by any appropriate adhesive. As the adhesive, for example, an adhesive using an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyether, a fluorine-based polymer or a rubber-based polymer as a base polymer is used. Preferably, an acrylic adhesive is used. The reason is that the acrylic adhesive has excellent optical transparency, exhibits appropriate adhesive properties of wettability, cohesion and adhesion, and can have excellent weather resistance and heat resistance. In particular, an acrylic adhesive made of an acrylic polymer having a carbon number of 4 to 12 is preferred.

[0079] There is no particular limitation on the thickness of the adhesive layer 14, and for example, it is about 1 to 400 μm. In addition, regarding the thickness of the adhesive layer 14, the preferred range can be appropriately set according to the method for manufacturing the (meth)acrylic polymer used for the adhesive. For example, in the case of manufacturing the (meth)acrylic polymer by solution polymerization, the thickness of the adhesive layer 14 is preferably 1 to 100 μm, more preferably 2 to 50 μm, further preferably 2 to 40 μm, and particularly preferably 5 to 35 μm. In addition, in the case of manufacturing the (meth)acrylic polymer by radiation polymerization, the thickness of the adhesive layer 14 is preferably 50 to 400 μm, more preferably 75 to 300 μm, and further preferably 100 to 200 μm. When manufacturing acrylic polymers of this thickness, solution polymerization is more suitable.

[0080] The elastic modulus of the adhesive layer 14 at 23° C. is preferably 0.00001 GPa to 10 GPa, more preferably 0.001 GPa to 8 GPa, and even more preferably 0.001 GPa to 5 GPa. Within this range, an optical film 10 having excellent flexibility and excellent puncture resistance can be obtained.

[0081] [Release film]

[0082] As described above, the release film is not a necessary structure, but is provided as needed. The release film can be formed, for example, of a resin of polyethylene terephthalate (PET). The thickness of the release film is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm, and further preferably 30 μm to 50 μm. Before the optical film 10 is attached to an optical element such as a liquid crystal unit, the release film is peeled off at the interface with the adhesive layer 14.

[0083] The optical film 10 can be used as a visual recognition side polarizing plate when constituting a liquid crystal panel, for example. In this case, the optical film 10 is disposed on the visual recognition side of the liquid crystal unit, for example, via an adhesive layer, and functions as a front surface plate of the liquid crystal panel. It should be noted that the visual recognition side refers to the side facing the visually recognized side when a predetermined component is applied to an image display device. The optical film 10 is preferably used, for example, for an in-cell type liquid crystal element. An in-cell type liquid crystal element is a liquid crystal element including a liquid crystal unit having a substrate in which a touch sensor is mounted.

[0084] [Extension of cracks in glass film]

[0085] If a crack of a predetermined size exists at the end of the glass film 11 , the crack may be extended due to expansion of the polarizing plate 13 or the like under a predetermined temperature and humidity environment, and it is preferable to suppress this.

[0086] According to the inventor's research, when the optical film 10 is commercialized, it is necessary to at least suppress the elongation of cracks at the ends of the glass film 11 in a constant temperature and humidity environment of 60°C and 90% humidity, and it is more preferred to suppress the elongation of cracks at the ends of the glass film 11 in a constant temperature and humidity environment of 80°C.

[0087] The inventors have discovered that in the optical film 10, by suppressing the absolute value of the difference between the strain in the MD direction and the strain in the TD direction of the polarizing plate 13 under a predetermined temperature and humidity environment, that is, the value of |MD-TD| within a predetermined range, even if a crack of a predetermined size exists at the end of the glass film 11, the elongation of the crack under a predetermined temperature and humidity environment can be suppressed.

[0088] Specifically, it is preferred that |MD-TD| of the polarizing plate 13 under a constant temperature and humidity environment of 60° C. and 90% be 0 or more and 40×10 -6 In addition, it is more preferable that |MD-TD| of the polarizing plate 13 in a heating environment test at a temperature of 80°C is 0 or more and 250×10 -6 the following.

[0089] By satisfying these requirements, the absolute value of the strain of the polarizing plate 13 becomes small, so the influence of the strain of the polarizing plate 13 on the glass film 11 is reduced, and even if there is a crack with a length of 20 μm or more at the end of the glass film 11, the elongation of the crack can be suppressed. In particular, when the polarizing plate 13 and the glass film 11 are bonded and integrated via a layer with a high elastic modulus such as the adhesive layer 12, a significant effect is exerted on the elongation of the crack.

[0090] The MD direction refers to the direction in which the molten resin flows inside the mold when the resin is melted and molded using the mold. The TD direction is a direction perpendicular to the MD direction.

[0091] In order to reduce the value of |MD-TD| of the polarizing plate 13 in a constant temperature and humidity environment at a temperature of 60°C and a humidity of 90% or in a heating environment test at a temperature of 80°C, the thickness of the polarizing plate 131 can be reduced. The thinner the thickness of the polarizing plate 131, the smaller the value of |MD-TD| of the polarizing plate 13 can be. The details of suppressing the elongation of cracks in the glass film will be described later in the embodiments.

[0092] <Second Embodiment>

[0093] The second embodiment shows an example of an optical film having a layer structure different from that of the first embodiment. In the second embodiment, description of components that are the same as those of the embodiments already described may be omitted.

[0094] Figure 2 FIG. 2 is a cross-sectional view showing an optical film according to the second embodiment. Figure 2 As shown, the optical film 10A and the optical film 10 (see Figure 1 ) is that the adhesive layer 12 is replaced by an adhesive layer 15.

[0095] The material of the adhesive layer 15 can be appropriately selected, for example, from the materials shown as the material of the adhesive layer 14. The thickness of the adhesive layer 15 is preferably greater than 20 μm and less than 500 μm. By setting the thickness of the adhesive layer 15 to be greater than 20 μm, the transmission of the strain of the polarizing plate 13 to the glass film 11 can be eased. Thus, even if there is a crack with a length of more than 20 μm at the end of the glass film 11, the elongation of the crack can be suppressed. In addition, by setting the thickness of the adhesive layer 15 to be less than 500 μm, the operability when manufacturing the optical film 10 using a roll-to-roll process can be improved.

[0096] Furthermore, the elastic modulus of the adhesive layer 15 at 25° C. is preferably 1.0×10 5 Pa or more and 5.5×10 6 Pa or less, more preferably 1.0×10 5 Pa or more and 1.0×10 6 Pa or less. By satisfying these requirements, the transmission of the strain of the polarizing plate 13 to the glass film 11 is further relaxed. Thus, even if a crack with a length of 20 μm or more exists at the end of the glass film 11, the extension of the crack can be further suppressed.

[0097] It should be noted that even when the adhesive layer 12 having a thickness of several μm is used for bonding the glass film 11 and the polarizing plate 13 as in the optical film 10 according to the first embodiment, if the elastic modulus of the adhesive layer 12 at 25° C. is 1.0×10 5 Pa or more and 5.5×10 6 Pa or less, the elongation of the crack can also be suppressed. In addition, if the elastic modulus of the adhesive layer 12 at 25°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less, the elongation of the crack can be further suppressed. The details of suppressing the elongation of the crack in the glass film will be described later in the examples.

[0098] [Example]

[0099] The optical film will be described in more detail below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples. In the Examples, "parts" and "%" are by weight unless otherwise specified.

[0100] [Manufacturing Example 1] Preparation of Polarizing Plate A

[0101] A polyvinyl alcohol film (PVA) with a thickness of 100 μm was dyed in a 0.3% iodine solution at 30°C for 1 minute between rollers with different speed ratios, and stretched to 3 times. Then, it was immersed in an aqueous solution containing 4% boric acid and 10% potassium iodide at 60°C for 0.5 minutes, and the comprehensive stretching ratio was stretched to 6 times. Next, it was washed by immersing it in an aqueous solution containing 1.5% potassium iodide at 30°C for 10 seconds, and then dried at 50°C for 4 minutes to obtain a polarizer with a thickness of 5 μm. An acrylic resin film with a thickness of 20 μm and an elastic modulus of 2.5 GPa was bonded to one surface of the polarizer using a polyvinyl alcohol-based adhesive to obtain a polarizing plate A (thickness: 25 μm).

[0102] [Manufacturing Example 2] Preparation of Polarizing Plate B

[0103] Polarizing plate B (thickness: 45 μm) was obtained in the same manner as in Production Example 1 except that an acrylic resin film having a thickness of 40 μm and an elastic modulus of 2.6 GPa was used.

[0104] [Manufacturing Example 3] Preparation of Polarizing Plate C

[0105] Polarizing plate C (thickness: 98 μm) was obtained in the same manner as in Manufacturing Example 1, except that the thickness of the polarizer was set to 28 μm, saponified triacetyl cellulose (TAC) with a thickness of 40 μm and an elastic modulus of 3.6 GPa was bonded to one surface of the polarizer using a polyvinyl alcohol-based adhesive, and an acrylic resin film with a thickness of 30 μm and an elastic modulus of 2.6 GPa was bonded to the other surface.

[0106] [Manufacturing Example 4] Preparation of Polarizing Plate D

[0107] Polarizing plate D (thickness: 88 μm) was obtained in the same manner as in Manufacturing Example 1, except that the thickness of the polarizer was set to 18 μm, saponified triacetyl cellulose (TAC) with a thickness of 40 μm and an elastic modulus of 3.6 GPa was bonded to one surface of the polarizer using a polyvinyl alcohol-based adhesive, and an acrylic resin film with a thickness of 30 μm and an elastic modulus of 2.6 GPa was bonded to the other surface.

[0108] [Manufacturing Example 5] Preparation of adhesive

[0109] (Preparation of acrylic polymer)

[0110] In a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a cooler, 100 parts by weight of butyl acrylate, 5 parts by weight of acrylic acid, 0.075 parts by weight of 2-hydroxyethyl acrylate, 0.2 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator, and 200 parts by weight of ethyl acetate as a polymerization solvent were placed, and nitrogen substitution was performed sufficiently. Then, while stirring under a nitrogen flow, the liquid temperature in the flask was maintained at about 55° C. and a polymerization reaction was performed for 10 hours to prepare an acrylic polymer solution. The weight average molecular weight of the acrylic polymer is 2.2 million.

[0111] (Preparation of Adhesive Composition)

[0112] In the above-mentioned acrylic polymer solution having a solid content of 100 parts by weight, 0.2 parts by weight of dibenzoyl peroxide (Nyper BMT, manufactured by NOF Corporation) as a peroxide, 0.05 parts by weight of diglycidylaminomethylcyclohexane (Tetrad C, manufactured by Mitsubishi Gas Chemical Co., Ltd.) as an epoxy crosslinking agent, 0.1 parts by weight of an adduct of trimethylolpropane / toluene diisocyanate (Coronate L, manufactured by Nippon Polyurethane Industries, Ltd.) as an isocyanate crosslinking agent, and 0.075 parts by weight of a silane coupling agent (KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) were uniformly mixed and stirred to prepare an acrylic adhesive (solid content of 10.9% by weight).

[0113] [Manufacturing Example 6] Preparation of Adhesive

[0114] (Preparation of epoxy adhesive)

[0115] An epoxy adhesive was prepared by mixing 70 parts by weight of Celloxide 2021P (manufactured by Daicel Chemical Industries, Ltd.), 5 parts by weight of EHPE3150, 19 parts by weight of Aron Oxetan OXT-221 (manufactured by Toagosei Co., Ltd.), 4 parts by weight of KBM-403 (manufactured by Shin-Etsu Chemical Co., Ltd.), and 2 parts by weight of CPI101A (manufactured by San-Apro Corporation).

[0116] <Examples 1, 2, Comparative Examples 1, 2>

[0117] [Example 1]

[0118] (Production of Optical Film A)

[0119] A 297 mm × 210 mm glass film (manufactured by Nippon Electric Glass Co., Ltd., trade name "OA-10G", thickness: 100 μm) and a 287 mm × 200 mm polarizing plate A prepared in Preparation Example 1 were bonded together via an adhesive layer composed of the adhesive prepared in Preparation Example 6. At this time, the polarizing plate A was arranged so that the acrylic film was located on the glass film side. Then, ultraviolet rays (500 mJ / cm 2 ) to harden the adhesive layer. The thickness of the adhesive layer is 2 μm and the elastic modulus is 1.8 GPa.

[0120] Next, an adhesive layer (thickness: 30 μm) composed of the adhesive prepared in Manufacturing Example 5 is formed on the surface of the optical film A on the opposite side of the polarizing plate A to the glass film, thereby obtaining an optical film. It should be noted that the adhesive layer is formed in the following manner. (i) It is coated on a siliconized polyethylene terephthalate film (manufactured by Mitsubishi Chemical Polyester Film Co., Ltd., thickness: 38 μm), and heated at 155° C. for 1 minute to form an adhesive layer with a thickness of 30 μm after drying, and (ii) The adhesive layer is transferred from the polyethylene terephthalate film to the polarizing plate A to form an adhesive layer.

[0121] [Example 2]

[0122] An optical film B was produced in the same manner as in Example 1, except that the polarizing plate B produced in Production Example 2 was used instead of the polarizing plate A produced in Production Example 1.

[0123] [Comparative Example 1]

[0124] Optical film C was produced in the same manner as in Example 1 except that polarizing plate C produced in Production Example 3 was used instead of polarizing plate A produced in Production Example 1. Polarizing plate D was disposed so that the triacetylcellulose film was located on the glass film side.

[0125] [Comparative Example 2]

[0126] Optical film C was produced in the same manner as in Example 1 except that polarizing plate D produced in Production Example 4 was used instead of polarizing plate A produced in Production Example 1. Polarizing plate D was disposed so that the triacetylcellulose film was located on the glass film side.

[0127] (Evaluation 1)

[0128] The strain amount and the like were measured for the optical film A obtained in Example 1. The details are shown below.

[0129] A diamond cutter was used to form a glass crack at the end of the glass film of the optical film A. Next, a 350×250mm×1.0mm thick alkali-free glass (Corning Incorporated, trade name "EG-XG") was prepared, and the optical film A processed into a 100mm square was attached to the alkali-free glass in such a way that the adhesive layer faced the alkali-free glass side. Next, the glass crack was extended from the end of the polarizing plate of the optical film A to the inside so that the length of the crack was 20μm or more.

[0130] Then, the optical film A was autoclaved at 50° C. and 0.5 MPa for 15 minutes to adhere the adhesive layer to the alkali-free glass. Then, before being subjected to a constant temperature and humidity test, the crack end was marked by visual inspection to obtain a sample A for evaluation.

[0131] Then, if Figure 3 As shown in FIG. 1 , a strain gauge 120 (FLA-3-11-3LJCT, manufactured by Tokyo Mekugi Laboratory Co., Ltd.) is attached to the evaluation sample A attached to the alkali-free glass 100 using a cyanoacrylate adhesive (AronAlpha, manufactured by Toagosei Co., Ltd.). The strain gauge 120 is attached so that the center of the strain gauge 120 is located 15 mm in the X direction and 15 mm in the Y direction from one corner of the evaluation sample A. At this time, the measurement axis of the strain gauge 120 (the long side direction of the strain gauge) is parallel to the absorption axis direction of the evaluation sample A, so that the strain amount in the direction orthogonal to the absorption axis direction of the polarizing plate can also be measured.

[0132] The lead wire of the strain gauge 120 is connected to a data recorder (TDS-530, manufactured by Tokyo Metering Laboratory Co., Ltd.), and the strain at room temperature (23°C) is adjusted to 0με, and then the evaluation sample A with the strain gauge 120 attached is placed in a constant temperature and humidity test (temperature is 60°C, humidity is 90%) for 15 minutes. Next, the strain during this period is measured every 15 seconds, and the strain at the 200-second time point (midpoint) is read and used as the strain of the evaluation sample A. In addition, the absolute value of (strain in the MD direction - strain in the TD direction) is used to calculate the difference in strain. In addition, a magnifying glass is used to visually determine the crack elongation.

[0133] The judgment criteria are as follows: ◎: the marked crack end has no elongation (qualified), ○: the elongation of the marked crack end is greater than 0 mm and less than or equal to 10 mm, and the elongation of the marked crack is less than 50% (qualified), △: the elongation of the marked crack end is greater than 0 mm and less than or equal to 10 mm, and the elongation of the marked crack is 50-75% (qualified), ×: the elongation of the marked crack end is greater than 10 mm (unqualified).

[0134] For the optical film B obtained in Example 2, the optical film C obtained in Comparative Example 1, and the optical film D obtained in Comparative Example 2, evaluation samples B to D were prepared in the same manner as for the optical film A, and the strain amount was measured, the difference in the strain amount was calculated, and the crack elongation was determined by visual inspection in the same manner as for the evaluation sample A. The evaluation results were displayed together with the structure of each evaluation sample. Figure 4 Shown in.

[0135] from Figure 4 It can be seen that by reducing the thickness of the polarizer, the absolute value of the difference between the strain in the MD direction and the strain in the TD direction of the polarizer under a constant temperature and humidity environment of 60°C and 90% humidity, i.e., the value of |MD-TD|, can be reduced. Moreover, the value of |MD-TD| of the polarizer under a constant temperature and humidity environment of 60°C and 90% humidity is preferably greater than 0 and less than 40×10 -6 If the value is within this range, it can be said that the elongation of cracks in the glass film can be suppressed. In addition, according to the results of Example 2, the value of |MD-TD| of the polarizing plate in a constant temperature and humidity environment of 60°C and 90% humidity is more preferably 0 or more and 10×10 -6 Hereinafter, within this range, it can be said that the extension of cracks in the glass film can be further suppressed.

[0136] <Examples 3 to 5, Comparative Example 3>

[0137] [Example 3]

[0138] In the same manner as in Example 1, an optical film E was obtained.

[0139] [Example 4]

[0140] In the same manner as in Example 2, an optical film F was obtained.

[0141] [Example 5]

[0142] Optical film G was produced in the same manner as in Example 1 except that polarizing plate D produced in Production Example 4 was used instead of polarizing plate A produced in Production Example 1. Polarizing plate D was disposed so that the triacetyl cellulose film was located on the glass film side.

[0143] [Comparative Example 3]

[0144] In the same manner as in Comparative Example 2, an optical film H was obtained.

[0145] (Evaluation 2)

[0146] The strain amount and the like were measured for the optical film E obtained in Example 3, the optical film F obtained in Example 4, the optical film G obtained in Example 5, and the optical film H obtained in Comparative Example 3. The details are as follows.

[0147] In the same manner as the evaluation sample A, evaluation samples E (Example 3), evaluation sample F (Example 4), evaluation sample G (Example 5), and evaluation sample H (Comparative Example 3) having cracks of 20 μm or more in length were prepared. Next, the strain amount was measured, the difference in strain amount was calculated, and the crack elongation was determined by visual inspection for evaluation samples E to H in the same manner as evaluation 1, except that the test conditions were changed from the constant temperature and humidity test (temperature: 60°C, humidity: 90%) to the heating environment test (temperature: 80°C). The evaluation results were presented together with the structure of each evaluation sample. Figure 5 Shown in.

[0148] from Figure 5 It can be seen that by reducing the thickness of the polarizer, the absolute value of the difference between the strain in the MD direction and the strain in the TD direction of the polarizer in a heating environment at a temperature of 80°C, that is, the value of |MD-TD|, can be reduced. In addition, the value of |MD-TD| of the polarizer in a heating environment at a temperature of 80°C is preferably greater than 0 and less than 250×10 -6 Hereinafter, within this range, it can be said that the extension of cracks in the glass film can be suppressed.

[0149] <Examples 6 to 8, Comparative Examples 4 and 5>

[0150] [Example 6]

[0151] Optical film I is prepared in the same manner as in Example 1, except that polarizing plate C prepared in Manufacturing Example 3 is used instead of polarizing plate A prepared in Manufacturing Example 1, and the triacetyl cellulose film side of polarizing plate C is bonded to the glass film by an adhesive layer (thickness: 2 μm, elastic modulus: 5.27 GPa) composed of the adhesive prepared in Manufacturing Example 6.

[0152] [Example 7]

[0153] Optical film J is prepared in the same manner as in Example 1, except that polarizing plate C prepared in Manufacturing Example 3 is used instead of polarizing plate A prepared in Manufacturing Example 1, and the triacetyl cellulose film side of polarizing plate C is bonded to the glass film by an adhesive layer (thickness: 20 μm, elastic modulus: 0.12 GPa) composed of the adhesive prepared in Manufacturing Example 5.

[0154] [Example 8]

[0155] Optical film K is prepared in the same manner as in Example 1, except that polarizing plate C prepared in Manufacturing Example 3 is used instead of polarizing plate A prepared in Manufacturing Example 1, and the triacetyl cellulose film side of polarizing plate C is bonded to the glass film by an adhesive layer (thickness: 250 μm, elastic modulus: 0.14 GPa) composed of the adhesive prepared in Manufacturing Example 5.

[0156] [Comparative Example 4]

[0157] Optical film L is prepared in the same manner as in Example 1, except that polarizing plate C prepared in Manufacturing Example 3 is used instead of polarizing plate A prepared in Manufacturing Example 1, and the triacetyl cellulose film side of polarizing plate C is bonded to the glass film by an adhesive layer (thickness: 2 μm, elastic modulus: 5.78 GPa) composed of the adhesive prepared in Manufacturing Example 6.

[0158] [Comparative Example 5]

[0159] Optical film M is prepared in the same manner as in Example 1, except that polarizing plate C prepared in Manufacturing Example 3 is used instead of polarizing plate A prepared in Manufacturing Example 1, and the triacetyl cellulose film side of polarizing plate C is bonded to the glass film by an adhesive layer (thickness: 2 μm, elastic modulus: 6.58 GPa) composed of the adhesive prepared in Manufacturing Example 6.

[0160] (Evaluation 3)

[0161] The optical film I obtained in Example 6, the optical film J obtained in Example 7, the optical film K obtained in Example 8, the optical film L obtained in Comparative Example 4, and the optical film M obtained in Comparative Example 5 were visually evaluated for crack extension in the same manner as in Evaluation 1. The details are as follows.

[0162] In the same manner as the evaluation sample A, evaluation samples I (Example 6), evaluation sample J (Example 7), evaluation sample K (Example 8), evaluation sample L (Comparative Example 4), and evaluation sample M (Comparative Example 5) having cracks with a length of 20 μm or more were prepared.

[0163] Next, the evaluation sample I was placed in a constant temperature and humidity test (temperature 60°C, humidity 90%) for 15 minutes, and then immediately taken out and the crack elongation was determined visually. The evaluation results and the structure of each evaluation sample were displayed on the Figure 6 It should be noted that Figure 6 The elastic modulus shown is the elastic modulus at 25°C.

[0164] exist Figure 6 In the above examples, the thickness of polarizer is 28μm. Figure 4 and Figure 5 As a result, it can be considered that |MD-TD| is the value of the crack elongation of the glass film in a constant temperature and humidity environment of 60°C and 90% humidity or in a heated environment of 80°C.

[0165] However, according to Figure 6 It can be said that even in this case, if the elastic modulus of the adhesive layer or the adhesive layer used to bond the glass film to the polarizing plate at 25°C is 1.0×10 5 Pa or more and 5.5×10 6 Pa or less, the elongation of cracks in the glass film can also be suppressed. In addition, it can be said that if the elastic modulus of the adhesive layer or the adhesive layer used to bond the glass film to the polarizing plate at 25°C is 1.0×10 5 Pa or more and 1.0×10 6 Pa or less, the extension of cracks in the glass film can be further suppressed.

[0166] In particular, if an adhesive layer having a thickness of 20 μm or more is used for bonding the glass film to the polarizing plate, the elastic modulus at 25°C can be set close to 1.0×10 5The value of Pa can be increased, and the extension of cracks in the glass film can be further suppressed. In view of workability when the optical film 10 is produced by a roll-to-roll process, the thickness of the adhesive layer is preferably 500 μm or less.

[0167] Summarizing the results of the above examples and comparative examples, it can be said that in order to suppress the extension of cracks in a glass film, it is preferable to satisfy the following requirements.

[0168] That is, it is preferred to reduce the thickness of the polarizer and set |MD-TD| to be greater than 0 and 40×10 -6 Below, and preferably, |MD-TD| in a heating environment test at a temperature of 80°C is set to be 0 or more and 250×10 -6 the following.

[0169] In addition, in order to suppress the elongation of cracks in the glass film, a countermeasure by selecting the characteristics of the adhesive layer or the adhesive layer may be adopted instead of reducing the thickness of the polarizer and setting |MD-TD| to a predetermined range. Specifically, it is preferred that the elastic modulus of the adhesive layer or the adhesive layer used to bond the glass film to the polarizer at 25°C be set to 1.0×10 5 Pa or more and 5.5×10 6 Pa or less, and more preferably 1.0×10 5 Pa or more and 1.0×10 6 Pa or less. In particular, when an adhesive layer having a thickness of 20 μm or more is used for bonding the glass film to the polarizing plate, the elastic modulus at 25° C. can be set to an extremely low value, which is preferred.

[0170] In order to suppress the extension of cracks in the glass film, a measure of reducing the thickness of the polarizer to set |MD-TD| within a predetermined range and a measure of selecting the properties of the adhesive layer or the pressure-sensitive adhesive layer to set the elastic modulus at 25°C within a predetermined range may be used in combination.

[0171] Although the preferred embodiments and the like have been described in detail above, the present invention is not limited to the above-described embodiments and the like, and various modifications and substitutions may be made to the above-described embodiments and the like without departing from the scope described in the claims.

[0172] This international application claims priority based on Japanese Patent Application No. 2019-177234 filed on September 27, 2019, and the entire contents of Japanese Patent Application No. 2019-177234 are cited in this international application.

Claims

1. An optical film, comprising a glass film and a polarizing plate, wherein: The glass film has a thickness of 50 μm or more and 150 μm or less. The glass film has a crack with a length of 20 μm or more at an end thereof, The polarizing plate comprises a polarizer and a protective film disposed on at least one surface of the polarizer. The polarizing plate has an absolute value of a difference between a strain amount in the MD direction and a strain amount in the TD direction under a constant temperature and humidity environment of 60° C. and 90% humidity, and is greater than or equal to 0 and less than 40×10 -6 the following, The glass film, the protective film, and the polarizer are stacked in this order, The glass film and the protective film are laminated via an adhesive layer or a pressure-sensitive adhesive layer. The tensile elastic modulus of the adhesive layer and the adhesive layer at 25° C. is 1.0×10 5 Pa or more and 5.5×10 6 Below Pa.

2. The optical film according to claim 1, wherein: The polarizing plate has an absolute value of a difference between a strain amount in the MD direction and a strain amount in the TD direction in a heating environment test at a temperature of 80° C. of 0 or more and a value of 250×10 -6 the following.

3. The optical film according to claim 1 or 2, wherein: The tensile elastic modulus of the adhesive layer and the adhesive layer at 25° C. is 1.0×10 5 Pa or more and 1.0×10 6 Below Pa.

4. The optical film according to claim 1 or 2, wherein: The thickness of the adhesive layer and the pressure-sensitive adhesive layer is 500 μm or less.

Citation Information

Patent Citations

  • Method for manufacturing film for optics

    JP2006309033A

  • Polarizer protective film, and polarizing plate using the same

    JP2006317560A

  • Base material for surface-protective film and surface-protective film

    JP2006328329A

  • Resin composition, optical film and polarizer protection film using the same

    JP2006328334A

  • Polarizer protecting film and polarizing plate using same

    JP2006337491A